2021
DOI: 10.1093/asjof/ojab010
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Fat Injection for Augmentation Rhinoplasty: A Systematic Review

Abstract: Background Autologous fat has become more frequently used for nasal volume augmentation and nasal correction. Nasal lipofilling refers to the use of injectable autologous fat grafts for nonsurgical aesthetic corrections. Objectives This systematic review aims to assess the satisfaction, complication, and retention rates of fat injection in nasal shape corrections. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…Previous studies showed high satisfaction with rates that range from 63% to 100% in this group of patients after the primary lipofilling of the nasal soft tissue 37,40,43,55 . This application of fat grafting is limited to non-major nasal deformities, and it has no known impact on the nasal respiratory function 37,38,40,57 .…”
Section: Primary Fat Grafting In Patients Who Wish To Avoid Surgical ...mentioning
confidence: 54%
See 4 more Smart Citations
“…Previous studies showed high satisfaction with rates that range from 63% to 100% in this group of patients after the primary lipofilling of the nasal soft tissue 37,40,43,55 . This application of fat grafting is limited to non-major nasal deformities, and it has no known impact on the nasal respiratory function 37,38,40,57 .…”
Section: Primary Fat Grafting In Patients Who Wish To Avoid Surgical ...mentioning
confidence: 54%
“…This aspirated fat is centrifuged and concentrated before injecting into the nasal SSTE. However, various planes for fat injection to the nose (e.g., at the periosteum and in the SMAS, subcutaneous, intradermal) and canula sizes have been described in the literature 40,43,54,55 .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 3 more Smart Citations